Medical equipment control system of the general hospital of Mexico. - Prieto Hernanadez, Fernando; Rodríguez Guerra, Jorge; Ronquillo Juárez, Carlos; Diaz Ceballos, Patricia (Revista Mexicana de Ingenieria Biomedica, 1991)
A program was developed in DBase, compiled with Clipper summer '87, to contain the information of about 2000 medical teams and more than 300 functional areas of the general hospital of Mexico, of the SSa. We faced a series of problems in obtaining, compiling and coding the data. The program has been a very useful instrument in the management of the hospital's medical team. The program is being adapted to the universal naming, coding and control systems of ECRI medical equipment.